Imaging findings of inflammatory myofibroblastic tumor of sigmoid colon: literature review and case report - Hu, Xianwen; Zhao, Wei; Yu, Ronghua; Wang, Pan (Frontiers in Medicine, 2024)
Inflammatory myofibroblastic tumor (IMT) is an intermediate tumor composed of differentiated myofibroblastic spindle cells with inflammatory cell infiltration. It can occur in all parts of the body, with the lungs being the most common, while the tissues outside the lungs, including the sigmoid colon, are rare. Herein, we present a case of a 10-year-old girl with sigmoid IMT who presented to our hospital with abdominal pain. An abdominal computed tomography (CT) revealed a well-defined, slightly low-density mass in her lower abdomen that was not clearly demarcated from the sigmoid colon. The mass showed significant uneven enhancement on contrast-enhanced CT and increased fluorine-18 fluorodeoxyglucose (18F-FDG) uptake on positron emission tomography (PET). Moreover, a systematic review of the published literature on sigmoid IMT was conducted and its clinical and radiographic features were summarized to increase the understanding of this rare disease.